2002
DOI: 10.2134/agronj2002.1530
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Management Strategies to Reduce Nitrate Leaching in Tile‐Drained Midwestern Soils

Abstract: Balancing the amount of N needed for optimum plant growth while minimizing the NO3 that is transported to ground and surface waters remains a major challenge for everyone attempting to understand and improve agricultural nutrient use efficiency. Our objectives for this review are to examine how changes in agricultural management practices during the past century have affected N in midwestern soils and to identify the types of research and management practices needed to reduce the potential for nonpoint NO3 lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
299
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 649 publications
(314 citation statements)
references
References 120 publications
(160 reference statements)
8
299
0
7
Order By: Relevance
“…Multiple cropping systems using cover crop or relay intercropping (group B) can mitigate nitrate losses by drainage. A typical winter cover crop can, for instance, decrease NO 3− leaching by 25 kg N ha −1 (Dabney et al 2001;Dinnes et al 2002). The main advantages of these systems over conventional crop sequences result from a combination of increased plant N capture throughout the year through nutrient cycling and N 2 fixation, reduced N fertilizer input, and a gradual release of organic N that is often better synchronized, than fertilizer application with crop demand and microbial population dynamics.…”
Section: Multiple Cropping Systems To Reduce Environmental Impactsmentioning
confidence: 99%
“…Multiple cropping systems using cover crop or relay intercropping (group B) can mitigate nitrate losses by drainage. A typical winter cover crop can, for instance, decrease NO 3− leaching by 25 kg N ha −1 (Dabney et al 2001;Dinnes et al 2002). The main advantages of these systems over conventional crop sequences result from a combination of increased plant N capture throughout the year through nutrient cycling and N 2 fixation, reduced N fertilizer input, and a gradual release of organic N that is often better synchronized, than fertilizer application with crop demand and microbial population dynamics.…”
Section: Multiple Cropping Systems To Reduce Environmental Impactsmentioning
confidence: 99%
“…In many (model) studies buffer strips were effective in reducing loads of N and P towards open water systems (e.g., PeterJohn and Correll 1984;Lowrance et al 1984;Orleans et al 1994;Vought et al 1994;Kuusemets et al 2001;Borin and Bigon 2002;Sabater et al 2003), but exceptions were found that were attributed to specific hydrological conditions or, for P, to the release of P due to reducing circumstances during wetting (LeedsHarrison et al 1999;Komor and Magner 1996). Dinnes et al (2002) reported efficiencies of buffer strips in reducing N and P loads of surface water of 48% to almost 100%. The efficiency was mainly related to the width of the buffer strip.…”
Section: Introductionmentioning
confidence: 99%
“…Also, current crop management practices result in the development of highly nitrifying soil environments (3,4). Nitrification results in the transformation of the relatively immobile NH 4 ϩ to highly mobile nitrate (NO 3 Ϫ ), making inorganic N susceptible to losses through leaching of NO 3 Ϫ and/or gaseous N emissions, potentially initiating a cascade of environmental and health problems (1,2,5,6). Nitrous oxide (N 2 O) is one of the three major biogenic greenhouse gases contributing to global warming, produced primarily from denitrification processes in agricultural systems (5,7).…”
mentioning
confidence: 99%